DEVELOPMENT OF ANIMATION VIDEO LEARNING MEDIA BASED ON PjBL USING CAPCUT APPLICATION ON THE THEME OF CARE FOR LIVING THINGS IN GRADE IV OF ELEMENTARY SCHOOL - Harahap, Habibah; Lestari, Nila (Media Inovasi Pendidikan dan Publikasi, 2025)
The purpose of this study is for students to understand and know the feasibility of learning media and understand problem solving with the material presented in the animated video learning media based on Project Based Learning (PjBL) using the CapCut application on the theme of caring for living things. This research is a Development or Research and Development (R&D) The model used in this development is the ADDIE model. The research subjects of this study were material expert validators, namely lecturers and teachers of grade IV of SD Negeri 1601 Sisalean and media experts, namely lecturers. The object of this study is animated video learning media based on PjB) using the CapCut application on the theme of caring for living things Based on the feasibility of the media from input from material experts, namely lecturers, media experts, namely lecturers, and student response questionnaires. From the validation data, material experts (lecturers) reached 88%, media experts (lecturers) reached 93% and student responses reached 85.5%. If the percentage obtained reaches 81% -100%, then the animated video learning media based on Project Based Learning (PjBL) using the CapCut application is categorized as very feasible. From the calculation above, the percentage of 88%, 93%, 85.5% is obtained, so the PjBL-based animated video learning media using the CapCut application is categorized as very feasible. Student learning outcomes after using PjBL-based animated video learning media using the CapCut application on the theme of caring for living things in grade IV of elementary school have increased with an N-gain value of 0.39 in the moderate category. This shows that PjBL-based animated video learning media using the CapCut application has a positive impact on student learning outcomes, although the influence of the media is still in the moderate category, it can be used to improve student learning outcomes. So the development of PjBL-based animated video learning media using the CapCut application on the theme of caring for living things in grade IV of elementary school developed by researchers is very feasible to use as a medium in learning.